Trade union recognition in Malaysia: Legal issues - Abd Razak, Siti Suraya; Nik Mahmod, Nik Ahmad Kamal (Universiti Utara Malaysia (UUM), 2018)
In Malaysia, the Federal Constitution protects the worker's enjoyment as to freedom of association, in particular, the right to form and join the trade union. However, due to security purposes, various restrictions have been imposed on trade union activities. The recognition process is currently showing a decline in the number of recognition awards due to the government's policy. This paper examines the legal issues and challenges confronting the trade union in the recognition process in Malaysia. This study adopted the qualitative approach to analyse the statutory procedures and cases relating to the issue. Interviews were conducted with the Department of Industrial Relations, Malaysia and the Department of Trade Union Affairs, Malaysia to obtain their opinion on the recognition process. It is suggested that the Malaysian government should abolish the employer's recognition; provide a statutory definition on the managerial, executive, confidential and security positions; establish an independent administrative trade union board and ratify the Convention Concerning Freedom of Association and Protection of the Right to Organise Convention No. 87. © 2018 UUM Journal of Legal Studies. ********************************************************* Di Malaysia, Perlembagaan Persekutuan melindungi kebebasan pekerja untuk berpersatuan, terutamanya, hak pekerja untuk menubuhkan dan menyertai kesatuan sekerja. Pelbagai sekatan telah dibuat ke atas aktiviti kesatuan sekerja demi faktor keselamatan. Kesan daripada polisi kerajaan, jumlah pengiktirafan yang berjaya menunjukkan kemerosotan. Kajian ini mengkaji isu undang-undang dan cabaran yang dihadapi oleh kesatuan sekerja dalam proses pengiktirafan kesatuan sekerja di Malaysia. Kajian ini menggunakan kaedah kualitatif untuk menganalisis prosedur-prosedur Akta dan kes-kes mahkamah yang berkaitan. Temu bual di Jabatan Perhubungan Perusahaan Malaysia dan Jabatan Kesatuan Sekerja telah dijalankan untuk mendapatkan pendapat mereka tentang proses pengiktirafan kesatuan sekerja secara keseluruhannya. Kajian ini mencadangkan supaya kerajaan Malaysia memansuhkan pengiktirafan majikan; memberikan definisi akta terhadap pengurusan, eksekutif, sulit dan keselamatan; menubuhkan badan bebas untuk menguruskan kesatuan sekerja serta mengiktiraf Konvensyen Kebebasan Persatuan dan Perlindungan Hak Menganjur No.87. © 2018 UUM Journal of Legal Studies.